Functionalized Cu3BiS3 nanoparticles for dual-modal imaging and targeted photothermal/photodynamic therapy. Issue 9 (16th February 2018) - Wang, Yanke; Cai, Dongdong; Wu, Huixia; Fu, Yu; Cao, Yang; Zhang, Yingjian; Wu, Dongmei; Tian, Qiwei; Yang, Shiping
Abstract : Multifunctional Cu3 BiS3 -PEG-(Ce6-Gd 3+ )-FA NPs were fabricated for tumour-targeted dual-modality CT/MR imaging and combined photothermal/photodynamic therapy. Abstract : Multifunctional nano-biomaterials with the integration of diagnostic and therapeutic functions have shown great promise in improving the efficacy of cancer therapy. Herein, a new nanoplatform based on functionalized Cu3 BiS3 nanoparticles (NPs) is fabricated for tumour-targeted combination phototherapy. The as-synthesized hydrophobic Cu3 BiS3 NPs are modified with DSPE-PEG/DSPE-PEG-NH2, followed by the conjugation of the photosensitizer chlorin e6 (Ce6) and the target ligand folic acid (FA). The introduced Ce6 can further form a chelate complex with Gd 3+ . The rationally designed Cu3 BiS3 -PEG-(Ce6-Gd 3+ )-FA NPs, which have high physiological stability and good biocompatibility, can specifically target FA-receptor over-expressed tumour cells. The Cu3 BiS3 -PEG-(Ce6-Gd 3+ )-FA NPs exhibit effective dual-modal CT and MR imaging in the xenografted HeLa tumours. Importantly, excellent in vivo anti-tumour effects have been achieved by synergistic photothermal/photodynamic therapy using the multifunctional NPs. We expect that this versatile nanoplatform will play a role in exploring precise cancer diagnosis and therapy.